Diabetes and tuberculosis, US National Health Interview Survey, 2000–2005 - Marks, S. M. (Int J Tuberc Lung Dis, 2011)
Blacks and Hispanics are disproportionately affected by diabetes, which may confound ethnic association with tuberculosis (TB). We analyzed 2000–2005 National Health Interview Survey data. We present adjusted odds ratios (aORs) and 99% confidence intervals (CIs) for the association of diabetes with history of TB disease, controlling for race/ethnicity and age. Diabetics had an aOR of 1.4 (99%CI 1.0–2.0) for history of TB, controlling for being foreign-born non-Hispanic (aOR 2.2, 99%CI 1.6–3.2), US-born Hispanic (aOR 2.1, 99%CI 1.4–3.2), age ≥65 years (aOR 2.0, 99%CI 1.5–2.6), and being Black (aOR 1.6, 99%CI 1.1–2.4). After controlling for race/ethnicity, self-identified diabetics had an increased aOR for history of TB.